ЖАМОАТ ХАВФСИЗЛИГИНИ ТАЪМИНЛАШ СОҲАСИДА КАДРЛАР ТАЙЁРЛАШДА ЖАНГОВАР ТАЙЁРГАРЛИКНИНГ АҲАМИЯТИ - Байдадаев, И.Ш. (SCIENCE and SOCIETY, 2024)
The article provides information about the features of the personnel training system in the field of ensuring public order and security, the latest reforms carried out in our country to develop the sphere and introduce relevant legal norms, as well as information about problems. on-site staff training and solutions.
Keywords: public safety; public order; combat training; paintball; airsoft; extreme situation